Ilex Paraguariensis Soil Sustainability Forestry Indicators in the Era of Biodiversity: A Case Study - Fasano, María Cecilia (2024)
Soil microbial diversity plays a pivotal role in maintaining forest ecosystem health, contributing to nutrient cycling, disease suppression, and overall soil fertility. As the demand for sustainable forestry practices increases, especially in plantations like Ilex paraguariensis, there is a critical need to develop new indicators or integrate soil microbial indicators into forest management frameworks. This manuscript explores the potential of soil microbial diversity as a core component of sustainable forestry management with a focus on I. paraguariensis, proposing novel indicators and practices tailored to enhance and monitor microbial edaphic health. We review current methodologies for assessing soil microbial diversity, including molecular techniques such as DNA sequencing and functional profiling in the context of forestry. The manuscript further presents case studies from various forest ecosystems where microbial diversity management has been successfully implemented. In addition, we propose a set of practical guidelines for forest managers of I. paraguariensis plantations to incorporate microbial health indicators into their landscape management strategies. These guidelines emphasize the importance of maintaining organic matter inputs, minimizing soil disturbance, and promoting native plant diversity to support robust edaphic microbial communities. Finally, by bridging the gap between microbial ecology and forest management, this manuscript aims to provide a framework for enhancing soil health and sustainability in I. paraguariensis plantations through the lens of microbial diversity.